2011
DOI: 10.1021/ac200726q
|View full text |Cite
|
Sign up to set email alerts
|

GlycoFish: A Database of Zebrafish N-linked Glycoproteins Identified Using SPEG Method Coupled with LC/MS

Abstract: Zebrafish (Danio rerio) is a model organism to study the mechanisms and pathways of human disorders. Many dysfunctions in neurological, development and neuromuscular systems are due to glycosylation deficiencies, but the glycoproteins involved in zebrafish embryonic development have not been established. In this study, a mass spectrometry-based glycoproteomic characterization of zebrafish embryos was performed to identify the N-linked glycoproteins and N-linked glycosylation sites. To increase the number of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Compared to previously reported atypical N -glycosites that were identified on the basis of the deamidation of asparagine residues after PNGase F treatment, 4,5 this study further validated the identified atypical motif glycosites by directly identifying their intact glycopeptides. Since the deamidation (N) can occur naturally and during sample preparation, direct identification of the intact glycopeptides with glycan attached is particularly important for confirmation of these atypical N -glycosylation sites detected by mass spectrometry-based glycoproteomics.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Compared to previously reported atypical N -glycosites that were identified on the basis of the deamidation of asparagine residues after PNGase F treatment, 4,5 this study further validated the identified atypical motif glycosites by directly identifying their intact glycopeptides. Since the deamidation (N) can occur naturally and during sample preparation, direct identification of the intact glycopeptides with glycan attached is particularly important for confirmation of these atypical N -glycosylation sites detected by mass spectrometry-based glycoproteomics.…”
supporting
confidence: 66%
“…Except for the N-X-C motif, which has been confirmed in several known glycoproteins, 3 all other atypical motifs were only identified on the basis of the deamidation of asparagine (N) residues in the peptides after PNGase F treatment (with/without 18O labeling) using mass spectrometry-based glycoproteomics. 4,5 However, the atypical sites identified on the basis of deamidation (N) are potentially false positives as deamidation (N) could occur naturally or be induced during sample preparation. 6,7 …”
mentioning
confidence: 99%
“…The lysates (800 μg) were denatured, reduced, alkylated and digested as previously explained 22 . Following tryptic digestion, the samples were desalted through C18 columns and were oxidized with 10 mM sodium periodate at room temperature in dark for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…A database for Drosophila N-linked glycopeptides (http://betenbaugh.jhu.edu/GlycoFly) named GlycoFly has been established as a resource for study of neurological disorders (Baycin-Hizal et al, 2011a). GlycoFish is a database of zebrafish N-linked glycoproteins (Baycin-Hizal et al, 2011b) and can be found at (http://betenbaugh.jhu.edu/ GlycoFish).…”
Section: B Databasesmentioning
confidence: 99%